Development of a planning support system to evaluate transit-oriented development masterplan concepts for optimal health outcomes. (November 2022) - Hooper, Paula; Bolleter, Julian; Edwards, Nicole
There is growing consensus that planning professionals need clearer guidance on features of the built environment that promote health benefits. Concomitantly, the smart city movement has created renewed opportunity and interest in data-driven urban modelling to support land use planning. Planning Support Systems (PSS) are spatially enabled computer-based analytical tools incorporating health-related metrics that apply empirical evidence on built environment relationships with health-related outcomes to inform real-world urban design, urban planning and transportation planning decisions. This paper presents the development of the Urban Health Check PSS to use local empirical data to explore and predict relative health impacts associated with proposed urban design planning changes from alternative new station precinct masterplan concepts. We present a case study where we compare a baseline scenario with alternative design concepts for a new train station precinct in Perth, Western Australia, that incorporated possible built environment interventions. Subsequently, we discuss potential future applications of health impact PSS for the translation and application of health evidence into practice.